2016
DOI: 10.1021/acs.jpclett.6b02024
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transport in Surface Diffusion of van der Waals Bonded Systems: Boosted by Rotations?

Abstract: Mass transport at a surface is a key factor in heterogeneous catalysis. The rate is determined by excitation across a translational barrier and depends on the energy landscape and the coupling to the thermal bath of the surface. Here we use helium spin− echo spectroscopy to track the microscopic motion of benzene adsorbed on Cu(001) at low coverage (θ ∼ 0.07 ML). Specifically, our combined experimental and computational data determine both the absolute rate and mechanism of the molecular motion. The observed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…The population of the rotated states would be expected to affect the pre-exponential factor for diffusion, rather than the Arrhenius activation energy that was considered in this work. A typical molecule’s trajectory across the surface would be expected to involve rotation as well as translation, but without the degree of coupling between the two that might be described in terms of quasi-static steering 10 where the molecule must rotate to pass over the rate-limiting barrier. 42 …”
Section: Computational Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The population of the rotated states would be expected to affect the pre-exponential factor for diffusion, rather than the Arrhenius activation energy that was considered in this work. A typical molecule’s trajectory across the surface would be expected to involve rotation as well as translation, but without the degree of coupling between the two that might be described in terms of quasi-static steering 10 where the molecule must rotate to pass over the rate-limiting barrier. 42 …”
Section: Computational Resultsmentioning
confidence: 99%
“…Benzene (>99.9% purity, Aldrich), purified by several freeze–evacuate–thaw cycles, was deposited on the surface by backfilling the chamber and monitoring the drop in the specularly reflected helium beam during adsorption. Using the same method as in our recent study of benzene on Cu(001), 10 we estimate absolute coverages of 0.03 and 0.1 monolayers (ML) for the low and high coverage measurements, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, pioneering works to study adsorption of larger molecules have demonstrated the need to consider dynamical degrees of freedom beyond translational diffusion in a 2D PES. [12,13] Here we describe PIGLE (Langevin Based Molecular Dynamics simulator), a package to simulate co-motion of interacting particles from multiple species in 2D to 4D PES (i.e. up to three spatial degrees of freedom, and rigid body rotations).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we focus on scanning probe microscopy techniques which have been used to characterize the surface diffusion of atoms and molecules on metals, [12][13][14][15][16][17][18] insulators 15,[19][20][21] and semiconductors 22,23 . Two main approaches have been adopted for determining associated energy barriers.…”
Section: Introductionmentioning
confidence: 99%